Low-temperature synthesis of nanocrystalline powders of lithium ferrite by an autocombustion method using citric acid and glycine - Verma, S.; Karande, J.; Patidar, A.; Joy, Pattayil Alias (Materials Letters, 2005)
Nanocrystalline lithium ferrite is synthesized by an autocombustion method from the corresponding metal nitrates using citric acid as well as glycine as fuels. The ordered phase of lithium ferrite, in single phase form, with particle size of 32-36 nm and large coercivity, is obtained by this method at a low temperature of 200 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Combustion synthesis; LiFe5O8; lithium ferrite; low-temperature synthesis; Magnetic materials; Nanomaterials